Perturbations of peripheral B lymphocyte homoeostasis in children with systemic lupus erythematosus. Issue 9 (15th August 2003) - Odendahl, M; Keitzer, R; Wahn, U; Hiepe, F; Radbruch, A; Dörner, T; Bunikowski, R
Abstract : Objective: To investigate the distribution of peripheral B cell subpopulations of children with active and inactive systemic lupus erythematosus (SLE) compared with healthy controls. Methods: Peripheral B cell subpopulations of 11 children with SLE (6 with active and 5 with inactive disease) and 14 age matched normal healthy children were analysed. Active disease was diagnosed in children with a flare of SLE, who received treatment by IV cyclophosphamide or IV methylprednisolone pulse to control the disease. Additionally, the peripheral B cells of the children with SLE were compared with those of 13 consecutive patients with adult onset SLE. Results: No major difference was found in the frequency and total number of CD27 − /CD19 + naïve B cells and CD27 + /CD19 + memory B cells between patients with active and inactive lupus and healthy controls, but there was a significant increase in CD27 high expressing plasma blasts in patients with active SLE. These cells coexpress CD38 +, HLA-DR dim, surface Ig low and lack the expression of CD20 but are clearly positive for intracellular Ig, indicative of early plasma cells. Most CD138 + cells coexpress CD27 high /CD19 + . The enhanced frequency of peripheral plasma blasts in children with active SLE is consistent with previous findings in adult patients with SLE, whereas a relative predominance of CD27 + memory B cells was only identified in the adult patients. Conclusions: Profound abnormalities in the distribution of B cell compartments are more pronounced in older patients with SLE, but an enhanced frequency and cell number of peripheral plasma blasts is characteristic of both diseases during active stages. Thus detection of CD27 high plasma blasts significantly correlates with active lupus in both children and adults.